A new four-pored Amphisbaena Linnaeus, 1758 (Amphisbaenia, Amphisbaenidae) from Brazilian Amazon - Oliveira, Elaine C.s.; Vaz-Silva, Wilian; Santos-Jr, Alfredo P.; Graboski, Roberta; Teixeira, Mauro Jr; Vechio, Francisco Dal; Ribeiro, Síria (Zootaxa, 2018)
A new species of Amphisbaena is described from the Brazilian Amazon, within the area impacted by the Teles Pires hydroelectric power plant, Jacareacanga municipality, State of Pará. Amphisbaena hoogmoedi sp. nov. can be diagnosed from its congeners by the following combination of characters: snout convex in profile view, sligthly compressed not keeled; pectoral scales arranged in regular annuli; conspicuous autotomic site between 7th–8th caudal annuli; 247–252 dorsal half-annuli; 27 caudal annuli; tail length 9.5–10.4% of snoutvent length; four precloacal pores arranged in sequence; three supralabials; a rounded tail; 22–24 dorsal segments in midbody annulus; postmalar row absent; head length 2.1–2.9% of snout-vent length; prefrontals length 46.6–49.5% of head length; prefrontals suture length 38–44.6% of head length; small malar length 10.6–13.4% of ventral length of head ; second infralabial length 33.8–38.5% of head length; ventral length of head 2.7–2.9% of snout-vent length; mouth length 80.2–81.8% of head length; third infralabial length 16.4–19.6% of head length; snout length 62.5–78.6% of head length; ocular length 23.4–26.2% of head length; mental length 23.2–25.4% of ventral length of head; postmental length 27.2–31.3% of ventral length of head; frontals suture length 23.4–32.3% of head length; postocular width 25–31.9% of maximun width of head; first supralabial length 24.9–30.6% of head length; second supralabial length 27.7–30% of head length and second supralabial height 26.9–28.8% of maximun head height. The hemipenis is bilobed, capitate and with lateral lamellae on the lobes; with a centrally-positioned spermatic groove, bifurcated at the base of the lobes, and with each branch extending to the tip of organ.